A Review on Impact of Agriculture on Deforestation (International Journal of Innovative Research in Engineering & Management, 2021)
Agriculture is a major driver of deforestation and has a significant  influence on deforestation. Because of the enormous population,  there is a great need for food, and in order to meet this demand,  wide-scale deforestation occurs. Food demand is high, which  encourages commercial farming and large-scale land purchase.  For large-scale cultivation, forests are being converted to  cropland. This has a negative impact on the ecosystem, climate,  and human health. Natural habitats and biodiversity are also  harmed. This review article examined the influence of agriculture  on deforestation while emphasizing the significance of  environmental conservation and health. This review included a  wide range of topics related to agricultural deforestation. Climate  change is currently the most pressing issue facing the globe,  which is why it is critical to expand the agriculture sector while  also implementing forest preservation policies that will assist to  secure and safeguard the environment.
Keywords: Agriculture; Commercial Farming; Climate Change; Deforestation; Land